(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Global migration is a complicated topic that requires coordinated, comprehensive strategies for efficient governance. The benefits and difficulties of coordinating immigration laws globally are examined in this essay. The diversity of migratory flows is one of the main obstacles. Various countries have various migration trends, from refugees escaping persecution or conflict to economic migrants looking for better prospects. Policies aimed at harmonizing must take into account these diverse situations while upholding national sovereignty.